2020
DOI: 10.1051/e3sconf/202017205009
|View full text |Cite
|
Sign up to set email alerts
|

Development of air tightness prediction method of masonry walls

Abstract: Recently, the construction of external walls of various blocks, which are externally insulated with mineral wool thermal insulation layer, with ventilated air gap and external finishing (ventilated wall structures) is becoming popular for public and office buildings. These blocks are used without internal rendering because they have a good interior surface, stable dimensions, and various filling of masonry joints provide an attractive architectural appearance. This reduces the cost and duration of construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…[21]. Besides, study of Paukštys et al indicated a hollow clay unit wall caused 7-11% less airtightness compared to a sand-lime block Wall unit [22]. It is known that the construction year of the building also has an effect on the airtightness performance.…”
Section: Multi-flat Buildings On the Floor One-flat Buildings On Floormentioning
confidence: 99%
“…[21]. Besides, study of Paukštys et al indicated a hollow clay unit wall caused 7-11% less airtightness compared to a sand-lime block Wall unit [22]. It is known that the construction year of the building also has an effect on the airtightness performance.…”
Section: Multi-flat Buildings On the Floor One-flat Buildings On Floormentioning
confidence: 99%
“…The final air leakage results were expressed as a rate of leakage per hour per square meter of the villa envelope at a reference pressure differential of 50 Pa (m 3 •h −1 •m −2 @50 Pa). This was calculated by dividing the total leakage flow rate (Q 50 ) by the envelope area (A E ) [39]. Thus:…”
Section: Air Permeabilitymentioning
confidence: 99%
“…Obviously, the leakage is apparent in the gaps of the frame, making significant infiltration. This was calculated by dividing the total leakage flow rate (Q50) by the envelope area (AE) [39]. Thus: AP50 = Q50/AE (3) where: Q50 = CL × 50 n , AP50 = air permeability, Q50 = air leakage rate at a pressure differences of 50 Pa, AE = envelope area m 2 , CL = air leakage coefficient, 50 n = differential pressure.…”
Section: Thermography Analysismentioning
confidence: 99%
See 1 more Smart Citation